Tanggung Jawab Debt Collector Dalam Hal Penyitaan Kendaraan Nasabah Kredit Macet - Alfata Fawwazi Muhammad; I Made Sarjana (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
The purpose of this study is to find out how the responsibility of a Debt Collector who is confiscating a bad credit vehicle is due to default from the debtor. The Debt Collector who carries out his duties cannot just arbitrarily withdraw the existing vehicle because it must comply with the applicable laws and regulations. Both creditors and debtors have fair legal protection. The debtor who makes a credit must also have the competence so that the credit is paid smoothly. If an act of default occurs, it can be prosecuted through civil law or if there is embezzlement of the motor vehicle used by the debtor, it can be prosecuted through criminal means. This article uses a normative research method whose approach is based on an approach to the legislation in force in Indonesia. Where in this normative research provides a view of how the Debt Collector should work according to the current law. Between the creditor and the debtor, there must be synchronization in carrying out their obligations so that there are no problems that lead to the withdrawal of the vehicle being used by the debtor. The fiduciary law that becomes the guarantor must be better understood by debtors who will make vehicle loans to better avoid the occurrence of the default act itself. Looking at the existing conditions, it is possible that many people who enter into credit agreements do not understand the importance of a law or law that applies in Indonesia. It is possible that if many people understand the law, the Leasing party no longer needs to use the services of a Debt Collector.